Políticas culturais de museus em Portugal: ciclos e processos de reflexão estratégica participada - José Soares Neves (Midas: Museus e Estudos Interdisciplinares)
Two cycles of cultural policies can be identified in democratic Portugal: one of growth until 2008 and another, afterwards, of crisis. In this article, in which I place the analytical focus on public policies for museums, I argue that a new cycle of growth seems to be drawn as from 2019. With this hypothesis in mind I revisit, in a comparative approach from the available literature and document analysis, especially legislation, two emblematic initiatives to reflect upon – the Project Structure that would lead to the foundation of the Portuguese Museum Network (RPM) in 2000, and the Museums in the Future Project Group in 2019. I conclude that participatory strategic thinking and funding are some of the main bases for sustaining the central public policies for museums in this new cycle. It is a new cycle more directed towards museums, palaces, and monuments under the tutelage of culture, but without forgetting the national museological panorama, i.e., the RPM's action through the defence of its revitalisation. In this regard, I discuss in more detail two major orientations of cultural policies – cultural democracy, which I associate with the RPM, and democratisation of culture, to which the GPMF is predominantly affiliated – and the participatory paradigm in public policies, present in both initiatives.